Report About the Design of External Fixator for Treatment of Pelvis and Acetabulum Fractures - Martin JANEČKA; Karel FRYDRÝŠEK; Leopold PLEVA; Jaroslav ROJÍČEK (Transactions of the VŠB-Technical University of Ostrava, Mechanical Series, 2012)
Main point in this contribution is the design of external fixators applied in traumatology and orthopaedics. These fixators can be used in the treatment of open and unstable (i.e. complicated) fractures of pelvis and its acetabulum. Numerical modelling (i.e. Finite Element Method), together with CAD modelling, experiments, material engineering, and nanotechnology are presented as a support for developing of a new design of external fixators.